Cytokine profile in Nigerians with tubal infertility (2016)
Background: Immune response to genital Chlamydia trachomatis infection is involved in both immunity and pathology. The cytokine profile during infection has been implicated in the disease outcome, either resolution or severe sequelae. Serum cytokines of Chlamydia positive Nigerian women with tubal infertility were assessed to determine their possible relationship with tubal occlusion. Material and methods: One hundred and fifty age-matched consenting women (100 fertile and 50 with tubal infertility) were recruited based on C. trachomatis antibody positivity and grouped into infertile Chlamydia positive (CTpos) women (n = 50), fertile Chlamydia positive women (n = 50) and fertile Chlamydia negative (CTneg) women as controls (n = 50). High vaginal swabs and endo-cervical swabs were collected for microscopy, culture and gram staining. Cytokines [transforming growth factor β1 (TG F-β1), interferon γ (IFN-γ), tumor necrosis factor α (TNF-α), interleukin (IL )-4, IL -10 and IL-17A] were estimated by ELISA in sera. Data were analyzed using ANOVA, χ2 and Spearman’s correlation at p = 0.05. Results: Lower IFN-γ levels were observed in infertile women compared to fertile women. Fertile CTneg women had significantly higher TNF-α, and TGF-β1 compared to fertile and infertile CTpos women, respectively. Lower IL-10 levels were seen in fertile CTpos women compared to the infertile CTpos group. Vaginal discharge was negatively correlated with TNF-α and IFN-γ and positively with IL-4 in Chlamydia positive women. Conclusions: Chlamydia positive women with tubal infertility have higher IL -10 and lower IFN-γ levels than controls, which may contribute to their development of tubal pathology.